Comparative analysis of the most popular databases - Morera M. A. (Students' science: current realities, 2018)
The most popular databases are considered. The analysis of various databases is accomplished, their advantages and disadvantages are revealed. Comparison of the cost of using databases, supported operating systems and licenses restricting their usage is done..
Keywords: база данных; СУБД; database; реляционная система; DBMS; relational system